2022
DOI: 10.1088/1748-9326/ac9cf4
|View full text |Cite
|
Sign up to set email alerts
|

Increases in China’s wind energy production from the recovery of wind speed since 2012

Abstract: China has realized a 56-fold increase in installed wind capacity, from 5.9 GW in 2007 to 328 GW in 2021. In addition to increasing installed capacity, plans to substantially increase wind energy production for climate change mitigation also depend on future wind speeds, which strongly influences the efficiencies of installed turbines within individual wind farms. A reversal in globally decreasing wind speeds over several decades has been reported previously. However, subsequent studies using other data sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In the station average time series, the breakpoint was detected in 2012 (P < 0.001) with a trend of -0.012 m s -1 year -1 (R 2 = 0.90, P <0.001) before and +0.013 m s -1 year -1 (R 2 = 0.70, P <0.01) after (Figure 5b). The increasing trend decreased by 41% after deleting those relocation-affected stations, compared with the +0.022 m s -1 year -1 in Figure 2b (also reported by Liu et al, 2022a). But the trend is larger than the +0.011 m s −1 yr −1 , reported by Yang et al (2021), with all the recorded location changed stations deleted without checking whether the station is affected by the relocation.…”
Section: Average Methods Used To Calculate the National Averagementioning
confidence: 79%
“…In the station average time series, the breakpoint was detected in 2012 (P < 0.001) with a trend of -0.012 m s -1 year -1 (R 2 = 0.90, P <0.001) before and +0.013 m s -1 year -1 (R 2 = 0.70, P <0.01) after (Figure 5b). The increasing trend decreased by 41% after deleting those relocation-affected stations, compared with the +0.022 m s -1 year -1 in Figure 2b (also reported by Liu et al, 2022a). But the trend is larger than the +0.011 m s −1 yr −1 , reported by Yang et al (2021), with all the recorded location changed stations deleted without checking whether the station is affected by the relocation.…”
Section: Average Methods Used To Calculate the National Averagementioning
confidence: 79%
“…For daily variation, the maximum gale events in North China occurred between 9:00 and 16:00 local time from the 1980s to the 2010s (Figure 3b). However, we find Observations revealed that the wind speed in North China suffered a decadal change in the past three decades, with a decline from 1990 and a recovery from 2008 [44]. Here, we further investigate the decadal change in temporal variation of gale events between 1980 and 2021 (Figure 3).…”
Section: Daily and Seasonal Variations Of Gale Eventsmentioning
confidence: 82%
“…Generally, after the ground is heated in the afternoon, the enhanced vertical exchange of air results in gales being transmitted from high levels to the ground. Observations revealed that the wind speed in North China suffered a decadal change in the past three decades, with a decline from 1990 and a recovery from 2008 [44]. Here, we further investigate the decadal change in temporal variation of gale events between 1980 and 2021 (Figure 3).…”
Section: Daily and Seasonal Variations Of Gale Eventsmentioning
confidence: 89%
“…However, to the authors' knowledge, there is only one study in the scientific literature that analyses surface wind speed in the frequency domain (Naizghi & Ouarda, 2017) despite all the insights that can be gained from a spectral analysis approach (Grinsted et al., 2004). The study of surface winds is of great socioeconomic and environmental importance for a large number of areas, with special emphasis on the production of electrical power (Liu et al., 2022). In 2019, the installed electricity capacity of wind power corresponded to approximately 25% of the total for the IP (European Commission and Directorate‐General for Energy, 2021).…”
Section: Introductionmentioning
confidence: 99%